1993
DOI: 10.1111/j.1911-3846.1993.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Ability of Audit Qualifications for Loss Contingencies*

Abstract: . Adequate disclosure of risks and uncertainties is an issue of interest to the accounting profession and regulators both in Canada and in the United States. Previously, auditors were required to modify their audit reports in the presence of material uncertainties. However, following suggestions that such disclosure is redundant and not useful, the CICA removed this requirement in 1980. Auditors in the United States are still required to disclose material uncertainties in the audit report. The criterion of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our evidence indicates that they did, suggesting that it may have been unwise to eliminate this reporting option since doing so curtails the ability of auditors to manage audit risk through the audit report choice. * In addition to being a vehicle for auditors to manage audit risk, there is also evidence that audit report modifications for material uncertainties convey new information to JKnancial statement users in the sense of having predictive ability (over and above required footnote disclosures) with respect to the future resolution of the uncertainties (Raghunandan 1993). In related research, Bamber and Stratton (1997) report an experiment in which modified reports for material uncertainties affected bank loan officers risk assessment, interest rate premium, and loan decisions.…”
Section: Us Audit Standards For Materials Uncertainties and Going Comentioning
confidence: 99%
“…Our evidence indicates that they did, suggesting that it may have been unwise to eliminate this reporting option since doing so curtails the ability of auditors to manage audit risk through the audit report choice. * In addition to being a vehicle for auditors to manage audit risk, there is also evidence that audit report modifications for material uncertainties convey new information to JKnancial statement users in the sense of having predictive ability (over and above required footnote disclosures) with respect to the future resolution of the uncertainties (Raghunandan 1993). In related research, Bamber and Stratton (1997) report an experiment in which modified reports for material uncertainties affected bank loan officers risk assessment, interest rate premium, and loan decisions.…”
Section: Us Audit Standards For Materials Uncertainties and Going Comentioning
confidence: 99%
“…5 However, subsequent studies reported the presence of such an association for audit qualifications that received media attention (Dopuch et al 1986), audit qualifications that were subsequently withdrawn (Fields and Wilkins 1991), audit qualifications that were unexpected (Loudder et al 1992), and audit qualifications for over-the-counter firms (Ameen et al 1994). As a result, Raghunandan (1993), and Bamber and Stratton (1997) have argued that since such audit qualifications have information content, the elimination of modified audit opinions in both Canada and the U.S. is not justified. We add to this literature by investigating whether auditor-disclosed qualifications in the form of quantifiable asset overstatements and/or liability nonrecognition or nondisclosure convey information to capital market participants.…”
Section: Related Prior Researchmentioning
confidence: 93%
“…Additionally, creditors may consider qualified opinions when making lending decisions (e.g., Guiral‐Contreras, Gonzalo‐Angulo, and Rodgers ), possibly because modified opinions often signal a decline in future earnings (Frost ). Raghunandan () even found that companies with modified opinions are more likely to receive an adverse resolution of pending litigation than similar companies that receive unqualified (“clean”) opinions. In summary, modified opinions can affect clients' cost of capital, market capitalization, and in some cases their ability to continue as a going concern (Wilkins ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%